PENGARUH IN STORE PROMOTION, STORE ATMOSPHERE, EMOSI POSITIF TERHADAP IMPULSE BUYING PADA KONSUMEN ROBINSON DEPARTEMENT STORE MAL CIPUTRA SEMARANG - Maylinda Nur Hasanah; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2018)
Impulse buying behavior can be affected by a variety of factors, both internal and external factors. The purpose of this research is to know the influence of the in store promotion, store atmosphere and positive emotion against impulse buying of the customer of Robinson Department Store at Mall Ciputra Semarang. The research type is explanatory research. This study uses purposive sampling techniques against the customer of Robinson Department Store at Mall Ciputra Semarang. Data collecting using a questionnaire and interviews. Data analysis using simple and doubled linier regression analysis using IBM SPSS 20. Results of statistical analysis known that together in store promotion, store atmosphere and positive emotion against impulse buying based on the coefficient of determination 48,7%, value F count (30,376) > F table (2,70) with significance of 0,000 > level of significance 0,05 then it can be seen that “ There is influence of in store promotion, store atmosphere and positive emotion to impulse buying. The conclusion from this study is that there is a positive and significant influence between in store promotion, store atmosphere and positive emotion to impulse buying of the customer of Robinson Department Store at Mall Ciputra Semarang. Research suggest that Robinson Department Store at Mall Ciputra Semarang improve quality of in store promotion and store atmosphere along with learn more about how to build positive emotion of consumers so that there is an increase in impulse buying by consumers.